Impact of altering proximity on snack food intake in individuals with high and low executive function: study protocol - Jennifer A. Hunter; Gareth J. Hollands; Dominique-Laurent Couturier; Theresa M. Marteau (BMC, 2016)
Abstract Background Despite attempts to improve diet at population level, people living in material and social deprivation continue to consume unhealthy diets. Executive function - the ability to regulate behaviour and resist impulses - is weaker in individuals living in deprivation. Dietary interventions that educate and persuade people to reflect on and actively change behaviour may therefore disproportionately benefit individuals who are socioeconomically advantaged and have stronger executive function, thus exacerbating inequalities in health resulting from unhealthy diets. In contrast, manipulating environmental cues, such as how far away a food is placed, does not appeal to reasoned action and is thought to operate largely outside of awareness to influence behaviour. People eat more of a food when it is placed closer to them, an effect seemingly robust to context, food quality and body-weight status. However, previous studies of this 'proximity effect' are limited by small samples consisting mainly of university staff or students, biased towards higher socio-economic position and therefore likely stronger executive function. This study aims to test the hypothesis that placing food further away from a person decreases intake of that food regardless of executive function. Methods/Design 156 members of the general public, recruited from low and high socio-economic groups, will be randomised to one of two conditions varying in the proximity of a snack food relative to their position: 20 cm or 70 cm. Participants are told they will be taking part in a relaxation study - and are fully debriefed at the conclusion of the session. The primary outcome is the proportion of participants eating any amount of snack food and the secondary outcome is the mean amount eaten. Executive function is assessed using the Stroop task. Discussion The proposed study takes a novel step by investigating the effect of proximity on snack food intake in a general population sample consisting of those with high and low executive function, appropriately powered to detect the predicted proximity effect. If this effect occurs irrespective of executive function and socio-economic position, it may have potential to reduce inequalities patterned by socio-economic position if implemented in real-world settings such as shops or restaurants. Trial registration Registered with the ISRCTN registry: ISRCTN46995850 on 07 October 2015.